Role of Immunomarkers in Diagnosis of Lung Carcinomas Using Small Lung Biopsies - daod, Ali kamel (Latakia University Journal -Medical Sciences Series, 2019)
A small lung biopsy through the bronchi is considered the main method to diagnose most of lung carcinomas. It`s essential to identify the different types of primary and metastatic lung carcinomas in order to apply the appropriate chemical and targeted therapies which depend in their efficacy on the accurate diagnosis of the type of the tumors. This study aims to determine the role of a selected group of immunohistochemical markers in confirming the diagnosis of primary lung carcinomas and distinguishing them from the metastatic ones. The study was performed on 145 small pulmonary biopsies, taken from the archive of department of pathology at Tishreen University Hospitalin Lattakia. All biopsies were stained with H&E and diagnosed depending of the histologic and morphologic standards. Then the selected immunohistochemical stainings ( P63 / p40, CD56, Chromogranin A, TTF1, Napsin-A, CK7, CK5 / 6, Desmoglin-3) were applied. The histomorphologic features were approached with the results of immunohistochemistry . The study showed that confirming the diagnosis of lung cancers requires the application of appropriate immunological markers, especially the poorly differentiated tumors. The compination of TTF1 with Napsin-A increased the diagnostic accuracy of adenocarcinoma from 75% to 95% . Furthermore, the combination of Desmoglin-3, with P63/P40 confirms thediagnosis of squamous cell carcinoma .Nonsmall cell lung carcinomas are a heterogeneous group that includes different tumors, which are distinguished with immunohistochemical markers تعتبر الخزعة الرئوية الصغيرة التنظيرية عبر القصبات هي الوسيلة الرئيسية لتشخيص معظم سرطانات الرئة. تمييز مختلف أنماط السرطانات الرئوية البدئية والنقيلية مهم من أجل تطبيق المعالجة الكيميائية والعلاجات الهدفية التي يتوقف نجاحها على تحديد النمط الخلوي للورم بدقة. تهدف الدراسة تحديد دور مجموعة انتقائية من الواسمات المناعية في تأكيد تشخيص السرطانات الرئوية البدئية وتمييزها عن النقائل. أجريت الدراسة على 145 خزعة رئوية صغيرة من ارشيف مخبر التشريح المرضي في مشفى تشرين الجامعي باللاذقية. شخصت جميع العينات بالاعتماد على المعايير النسيجية والمورفولوجية وبطريقة التلوين الروتيني بـ H&E , ثم طبقت الواسمات المناعية المنتقاة P63/p40, CD56, Chromogranin A, TTF1, Napsin-A, CK7,CK5/6, Desmoglin-3 . تمت مقاربة العلامات المورفولوجية النسيجية لكل ورم مع نتائج الواسمات المناعية. بينت الدراسة أن تأكيد تشخيص سرطانات الرئة يتطلب تطبيق الواسمات المناعية المناسبة وخاصة الحالات القليلة التمايز. ترفع مشاركة TTF1, مع Napsin-A دقة تشخيص السرطان الغدي الرئوي من 75% إلى 95% , وأن مشاركة Desmoglin-3مع P63/p40, تؤكد تشخيص السرطان شائك الخلايا. المجموعة المسماة سرطانات غير صغيرة الخلايا هي مجموعة متغايرة تضم أوراما مختلفة يتم تمييزها بواسطة الواسمات المناعية.